Kontribusi Minat Kedisiplinan Dan Kelengkapan Fasilitas Belajar Terhadap Kemandirian Belajar Siswa Kelas Xi Smk Cokroaminoto 1 Surakarta Tahun Pelajaran 2013/2014 - Aslam Bakhtiar, Mega; , Prof. Dr. Sutama, M.Pd (2017)
Mega Aslam Bakhtiar. NIM. Q100110092. 2013. Contribution of Interests, Discipline, and Completeness Facilities to Autonomic Learning Student of Class XI Subject RPL SMK Tjokroaminoto I Surakarta academic year 2013/2014. 90 pages. From preliminary observations in SMK Tjokroaminoto 1 Surakarta lack of autonomy seems to solve the problem of students in each. There are many factors which affect autonomy in learning. The purpose of this study wanted to determine the contribution of interest, discipline, and completeness of learning facilities to autonomic learning. Data was collected through questionnaire method is given to a number of respondents, 16 students. Before use, the questionnaire was tested for validity and reliability. After the data collected were tested for normality and linearity. Furthermore, the data were analyzed with multiple linear regression statistical tests three predictors through the aid program SPSS or MS Excel count. Regression line equation is obtained . With a significance level of 5% by F test turns out there are three variables influence learning interest, learning discipline and completeness learning facilities together towards autonomic learning variable. As partial to determine the effect of each independent variable to the dependent variable using the t test. From the t-test results obtained that there is interest in studying the effect of autonomic learning variable, but there was no effect of variable learning discipline and completeness learning facilities individually against autonomic learning variable. This research may not depict the actual situation, therefore, is an opportunity for other researchers to conduct re-test with a representative number of respondents Keywords: Interests, Discipline, Completeness Learning Facilities, Autonomic Learning.